(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The previous few decades have seen exceptional advances in the utilization of composite materials in structural applications. Structural members that are comprised of at least two distinct materials are known as composite elements. The principle advantage of composite elements is that the properties of every material can be joined to frame a solitary unit that performs preferable generally speaking over its different constituent parts. Composite columns are a blend of two customary underlying structures: primary steel and primary cement. As composite columns were by and large created after steel columns and supported concrete columns, their plan approach might have been founded on one or the other steel or substantial plan techniques. In this thesis G+10, G15, G+30 storey conventional building models are been compared with composite column and compared their behaviour under zone III seismic condition using etabs. Change in the shape and size of composite column gives better result.